MO862: Humoral Response to a Third Dose of the MRNA-1273 Vaccine in Haemodialysis Patients. (3rd May 2022) - Tsalouchos, Aris; Laudicina, Selene; Semeraro, Francesca; Vignali, Lorenzo; Zullo, Claudia; Gallo, Pamela; Ferro, Giuseppe; Dattolo, Pietro
Abstract: BACKGROUND: Adults receiving haemodialysis (HD) have a higher mortality risk when infected with SARS-CoV-2 and less intense humoral response after two doses of mRNA vaccines compared with healthy subjects [1 ], leading the Italian authorities to recommend a third dose as a priority in this high-risk population. Here we investigated the humoral response to the third dose of the mRNA-1273 vaccine in a cohort of HD patients. METHODS: Observational cohort data were collected from our HD centre. A third dose of the mRNA-1273 vaccine was proposed to all HD patients regardless of the anti-S1-RBD IgG titres measured at a median two weeks before the scheduled injection, and regardless of previously developed COVID-19. All patients received two doses of the mRNA-1273 vaccine in March-April 2021. As per the suggested policy, the third dose was administrated 6 months after the second dose. The primary endpoint was the humoral response at least four weeks after the third dose of vaccine compared with the anti-S1-RBD IgG titre measured two weeks before the vaccine administration. Anti-S1-RBD IgG titres were determined using a fluoroimmunoenzymatic method (Thermo Fisher Scientific), and the quantitative result expressed in BAU/mL (reference interval: <28 Negative; 28–40 Borderline; >40 Positive; linear range between 0.7 and >1632 according to the manufacturer). RESULTS: Among the 66 HD patients who received two mRNA-1273 doses, 2 (3%) developed COVID-19 after the second dose of vaccine, and two patients refused the third injection. Thus, 64 patients received the third dose (Figure 1 ). At baseline, anti-S1-RBD IgG titres were measured at a median of 12 days (IQR 10–15) before the third vaccine dose. The median level of anti-S1-RBD IgG was 208 BAU/mL (IQR 0.7–>1632). Negative, borderline and positive responses were observed in 16 (24.2%), 2 (3%) and 48 (72.7%) patients, respectively. After the third vaccine dose, anti-S1-RBD IgG titres were measured at a median of 43 days (IQR 40–49). The median anti-S1-RBD IgG titre significantly increased after the third dose (>1632 versus 142; P < 0.0001). After the third dose, 61/64 (95.3%) patients were responders. The primary composite endpoint (defined as the cumulative percentage of patients switching from negative to responder status, from borderline to responder status, and at least low titre positive patients doubling their S1-RBD IgG titre), was reached in 60/64 (93.75%) patients. In detail, 13/16 (81.25%) changed from negative to responder status, 2/2 (100%) from borderline to responder, and 45/46 (97.82%) at least doubled their anti-S1-RBD IgG titre (Figure 1 ). Figure 2 shows the kinetics of anti-S1-RBD IgG titres before and after the third dose according to the response status before the third dose. Among the three patients, who did not mount an antibody response, two of them were on immunosuppressive therapy the third was an older patient (89 years). CONCLUSIONS: In this study, a third dose of the mRNA-1273 vaccine substantially increased antibody levels in HD patients, consolidating the humoral response against SARS-CoV-2 in a population known to have a rapid antibody decline after vaccination [1, 3 ]. Furthermore, the third dose allowed seroconversion in those patients without a protective antibody titre after about 6 months of the conventional vaccination schedule. Thus, intensification of the vaccination protocol appears to be a reliable strategy for strengthening protection against SARS-CoV-2 in HD patients.